2009
DOI: 10.1097/ijg.0b013e31818fb434
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Brinzolamide 1%/Timolol 0.5% Fixed Combination Versus Dorzolamide 2%/Timolol 0.5% in Patients With Open-angle Glaucoma or Ocular Hypertension

Abstract: Brinz/Tim suspension provides statistically significant and clinically relevant IOP-lowering efficacy that is noninferior to Dorz/Tim. Additionally, Brinz/Tim affords an ocular comfort advantage compared with Dorz/Tim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 27 publications
9
54
1
8
Order By: Relevance
“…2009). In a study by Manni et al., BTFC or 2% DTFC was applied alone to the eyes of patients with OH or OAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009). In a study by Manni et al., BTFC or 2% DTFC was applied alone to the eyes of patients with OH or OAG.…”
Section: Discussionmentioning
confidence: 99%
“…This non‐inferiority margin (1.5 mmHg) was selected from a previous study with a similar design (Manni et al. 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Desses pacientes, dois queixaram de ardência (7,7%), um de embaçamento (3,8%) e um de leve queimação (3,8%). Na literatura encontramos estudos que comparam uma medicação com outra, onde em todas as comparações apresentaram resultados favorá-veis à combinação de timolol com brinzolamida (5,10,11) . A combinação de timolol 0,5% com brinzolamida 1% mostrou-se eficaz no controle da PIO com índices de redução semelhantes à literatura e mostrou um baixo índice de desconforto nos pacientes acompanhados.…”
Section: Discussionunclassified
“…The impact of physiological pH on compliance has recently been accentuated by the makers of Azarga. 25,24 However, this claim was only compared with Cosopt, and not set in the context of a survey of the pH of all other glaucoma products. The lack of easily available information regarding the pH of commonly used glaucoma medications was the main motivation for this study.…”
Section: Clinical Relevancementioning
confidence: 99%
“…A patient preference study found greater comfort associated with the physiological pH of the brinzolamide-based suspensions compared with the more acidic dorzolamide-based solutions and concluded that differences in ocular discomfort and adverse effects were likely to be attributable to the pH and formulation differences given the similarities of the active ingredients in the two combination products investigated. 24,23 In other words, excipients could have a role in patient tolerance and subsequent therapeutic compliance, independent of preservatives.…”
Section: Chemical Composition (Ph)mentioning
confidence: 99%